Bioactive Compounds, Antioxidant Capacity and HMG-CoA Reductase Inhibitory Potential of Red Fruit Oil (Pandanus conoideus Lam.): An In Silico and In Vitro Study - Tande, Ribka; Rimbawan, Rimbawan; Palupi, Eny; Kurniasih, Rini; Haerati, Nur (Universitas Gadjah Mada, 2026)
Cardiovascular disease, the leading cause of death worldwide, can result from dyslipidemia's ability to promote atherosclerosis. Therefore, it is important to address this issue by utilizing local food sources, such as red fruit oil, an endemic fruit from Papua, Indonesia. Red fruit oil contains some bioactive compounds, making it a promising candidate for use in functional foods. This study aimed to assess the bioactive components of red fruit oil, its antioxidant capacity, and its inhibitory potential against 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) reductase enzyme, both in silico and in vitro. The results showed that red fruit oil contained total phenolics of 627.42 ± 61.78 mg GAE/g, flavonoids of 128.06 ± 8.94 mg QE/g, and an antioxidant capacity of 2316.15 ± 135.63 μmol TE/g. Based on the outcomes of in silico investigations, the suspected compounds capable of inhibiting HMG-CoA reductase were isochamaejasm, 6-acetylpicropolin, (−)-pinellic acid, and 2-monolinolein, with binding energies of −8.3620, −7.9660, −7.6980, and −7.6970 kcal/mol, respectively. The in vitro results showed that the inhibitory activity of red fruit oil was 48.36 ± 2.46, which was not significantly different from that of lovastatin 50.82 ± 2.46 (p = 0.288). The findings of this study suggest that red fruit oil may be able to manage dyslipidemia by inhibiting HMG-CoA reductase.